Prognostic Factors and Models for Changes in Cognitive Performance After Multi-Domain Cognitive Training in Healthy Older Adults: A Systematic Review - Roheger, Mandy; Liebermann-Jordanidis, Hannah; Krohm, Fabian; Adams, Anne; Kalbe, Elke (Frontiers in Human Neuroscience, 2021)
Background: Cognitive Training (CT) may contribute to the maintenance and even enhancement of cognitive functions in healthy older adults. However, the question who benefits most from multi-domain CTs is still highly under-investigated. Objective: The goal is to investigate prognostic factors and models for changes in cognitive test performance in healthy older adults after a multi-domain CT. Methods: The data bases MEDLINE, Web of Science Core Collection, CENTRAL, and PsycInfo were searched up to July 2019. Studies investigating prognostic factors and/or models on cognitive outcomes (global cognition, memory, attention, executive functions, language, visuo-spatial abilities) after conducting a multi-domain CT in healthy older adults were included. Risk of Bias was assessed using the QUIPS and the PROBAST tool. Results: 23 prognostic factor and model studies were included. Results indicate a high heterogeneity regarding the conducted multi-domain CTs, the investigated prognostic factors, the investigated outcomes, and the used statistical approaches. Age and neuropsychological performance at study entry were the most investigated predictors, yet they show inconsistent results. Conclusion: Data on prognostic factors and models of changes after multi-domain CT are still too rare and inconsistent to draw clear conclusions due to statistical shortcomings and low reporting quality. Approaches for future research are outlined. Registration: https://www.crd.york.ac.uk/prospero/, ID: CRD42020147531